Placental expression of adenosine A2A receptor and hypoxia inducible factor-1 alpha in early pregnancy, term and pre-eclamptic pregnancies: interactions with placental renin-angiotensin system - Kurlak, L.O.; Williams, Paula Juliet; Bulmer, Judith N.; Broughton Pipkin, Fiona; Mistry, Hiten D. (Elsevier, 2015)
Normal placentation occurs under low oxygen tensions yet hypoxia is also implicated in placental pathologies such as pre-eclampsia (PE). Hypoxia-inducible factors (HIFs), adenosine and tissue renin-angiotensin-system (RAS) are known to promote angiogenesis and vascularisation. We hypothesised that placental adenosine A2AR receptor and HIF-1α would change through pregnancy in association with the RAS. Placentae were obtained from women undergoing elective surgical termination of pregnancy (TOP) at ≤10 weeks’ (early TOP) and >10 weeks’ (mid TOP) gestations; at delivery from normotensive (NT) and PE pregnancy. Results were compared to our previously reported data on the angiotensin receptors: AT1R, AT2R and AT4R. Protein expression of both A2AR and HIF-1α was highest in early TOP and positively correlated through pregnancy (P<0.0001): expression was higher in PE than NT at delivery (P<0.0001 for both). The A2AR positively correlated with the AT4R in placentae in early pregnancy (r=0.53; P=0.035), but not in 3rd trimester samples. Our findings suggest a role for adenosine and RAS in promoting placentation and as a potential adaptation to poor placental perfusion in pre-eclampsia.